Pergeseran Penerjemahan dalam Penerjemahan Manga "Kimi No Ga Daidaidaidaidai Suki Na 100-Nin No Kanojo" - Michael, Michael; Arfianty, Rani (Jurnal SORA - Pernik Studi Bahasa Asing, 2024)
This study is focused into shift in translation, to study the shift in the English translation translation of “Kimi no Koto ga Daidaidaidaidai Suki na 100-nin no Kanojo” manga. In translation process, there is text that can be directly translated into target language, but sometimes it needs to be adjusted or omitted by changing the phrase, clause, or sentence which is called shift in translation. Specifically, in a language where the grammatical structure differs from each other’s. For example, Japanese with Indonesian. The data will be identified utilizing Catford’s shift in translation theorem. With qualitative methods the data will be analyzed from the conversations between characters. This study discovers five types of shifts, which is: (1) level shift that occurs when the lexical and grammatical meaning from translation differs; (2) structure shift that occurs if the order of grammatical structure is different; (3) word class shift that occurs when the word class change for example from verb into noun; (4) unit shift that occurs when the phrase becomes clause, clause into sentence, etc. And lastly (5) intra system shift that occurs when the grammatical structure cause the translation to shift.